2021
DOI: 10.3389/fimmu.2021.765382
|View full text |Cite
|
Sign up to set email alerts
|

An Oxidative Stress-Related Gene Pair (CCNB1/PKD1), Competitive Endogenous RNAs, and Immune-Infiltration Patterns Potentially Regulate Intervertebral Disc Degeneration Development

Abstract: Oxidative stress (OS) irreversibly affects the pathogenesis of intervertebral disc degeneration (IDD). Certain non-coding RNAs act as competitive endogenous RNAs (ceRNAs) that regulate IDD progression. Analyzing the signatures of oxidative stress-related gene (OSRG) pairs and regulatory ceRNA mechanisms and immune-infiltration patterns associated with IDD may enable researchers to distinguish IDD and reveal the underlying mechanisms. In this study, OSRGs were downloaded and identified using the Gene Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Continuous variables were expressed as mean ± SD, and differences between two groups were compared using Student’s t-test for normally distributed variables and Mann–Whitney U test for abnormally distributed variables. Differential expression analysis was performed with the cut-off thresholds of P < 0.05 and |log 2 FC| > 0.58 or |FC| > 1.5, which was consistent with previously reported methods [ 36 , 37 ]. For each study, P < 0.05 was considered as a significant difference.…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…Continuous variables were expressed as mean ± SD, and differences between two groups were compared using Student’s t-test for normally distributed variables and Mann–Whitney U test for abnormally distributed variables. Differential expression analysis was performed with the cut-off thresholds of P < 0.05 and |log 2 FC| > 0.58 or |FC| > 1.5, which was consistent with previously reported methods [ 36 , 37 ]. For each study, P < 0.05 was considered as a significant difference.…”
Section: Methodsmentioning
confidence: 71%
“…Using R’s “ limma (v3.42.2) ” package to identify differential expressed mRNAs (DEmRNAs) and lncRNAs (DElncRNAs) between IS and control samples. The P < 0.05, |log 2 fold change (FC)| > 0.58 or |FC| > 1.5 were selected as the cut-off thresholds, in accordance with previously reported methods [ 36 , 37 ]. Among DEmRNAs, we took the DEmRNAs that were overlapped with the ferroptosis-related genes as the differentially expressed ferroptosis-related genes (DEFRGs).…”
Section: Methodsmentioning
confidence: 99%
“…Polo like kinase 1 (PLK 1) plays an important role in the regulation of the cytoskeleton network during mitosis (32), and li et al demonstrated PLK1 expression was decreased in NPCs of degenerative IVDs (33). In addition, CCNB1 is a member of cyclin family, which is responsible for cell proliferation and differentiation (34). Its elimination inhibits the proliferation of IVD cells, revealing that CCNB1 is an important regulator of the G2/M phase of NP cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…Usually called CD8+T cells are CTLs, its main function is to kill target cells. Recent studies have indicated that CD8 T cells in rat IDD models are more prone to apoptosis, and CD8 T cells play a role in the pathogenesis of IDD and apoptosis (Li et al, 2020a;Cao et al, 2021). T cells gamma delta (Tgd) is a unique group of lymphocytes that are often enriched on the surface of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%